Circummaxillary Sutures in Patients With Apert, Crouzon, and Pfeiffer Syndromes Compared to Nonsyndromic Children: Growth, Orthodontic, and Surgical Implications. (March 2021) - Meazzini, Maria Costanza; Corradi, Federica; Mazzoleni, Fabio; De Ponti, Elena; Maccagni, Muriel; Novelli, Giorgio; Bozzetti, Alberto
Objective: To evaluate patency of circummaxillary sutures in children with Apert, Crouzon, and Pfeiffer Syndromes and to compare it to a nonsyndromic matched control group. Design: Case–control study. Setting: Tertiary care public hospital. Materials and Methods: Thirty-eight computed tomography (CT) scans of patients affected by syndromic craniofacial synostosis (13 patients with Apert syndrome, 20 patients with Crouzon syndrome, and 5 patients with Pfeiffer syndrome), average age 5 ± 2.8 years, range 1.9 to 12 years, were compared to age- and sex-matched control CTs of 38 nonsyndromic children. Computed tomography scans of the study group had to be performed prior to any midfacial surgery. Main Outcome Measures: Midpalatal suture, zygomaticomaxillary sutures, and pterigomaxillary sutures were evaluated and scored. Results: The syndromic group showed a significant earlier ossification of all sutures compared to the nonsyndromic group. Significant differences were already present in early childhood and continued through adolescence. Conclusions: Based on the differences in terms of maxillary sutural ossification identified, midfacial hypoplasia does not seem to be only secondary to premature cranial base ossification, but also to primary synostosis of facial sutures, thus providing new insights into the pathogenesis of midface deficiency in children with craniofacial-synostosis. Care should be taken when planning any maxillary orthopedics, such as expansion or maxillary protraction, given the high frequency of early fusion of circummaxillary sutures.